Synthesis, characterization, and properties of vinyl‐terminated copolysiloxanes containing trifluoropropyl and 4‐trifluoromethylphenyl groups. Issue 8 (1st February 2015) - Fei, Hua‐Feng; Gao, Xiyin; Han, Xiaojie; Wang, Qian; Hu, Tao; Zhang, Zhijie; Xie, Zemin
ABSTRACT Novel fluorine containing siloxane monomer, namely, 4‐trifluoromethylphenylmethyl cyclosiloxane (PF3) and mixed cyclosiloxane including both 4‐trifluoromethylphenylmethyl siloxane (P) unit and trifluoropropyl siloxane (F) unit were successfully synthesized in this study. Furthermore, their series including vinyl‐terminated copolymers with different compositions were synthesized. The microstructures of copolymers were investigated by 1H NMR, 29Si NMR, 19F NMR, Fourier transform infrared spectroscopy, and differential scanning calorimetry (DSC). The results of characterizations confirmed that the copolymers exhibited random microstructure. Moreover, the analysis of the result of DSC also revealed that the copolymers had a low glass transition temperature. The thermogravimetric analysis indicated that poly(4‐trifluoromethylphenylmethyl)siloxane (PPF3) exhibited higher thermal stability than conventional fluorosilicones rubber (FSR). The dynamic mechanical analysis showed that the damping factors of these copolymers were greater than 0.3 in a wide range of temperature. The mass swelling ratios were less than 5.5% when the samples were immersed in No. 3 jet fuel for a month. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 1023–1031